THE NARRATOR IN DORIS LESSING’S THE FIFTH CHILD - Cui, Zhenhua; Yang, Yanping; Yang, Yanping (Advances in Social Sciences Research Journal, 2020)
This paper reviewed the theoretic classification on narrator of fictions. The narrator of THE FIFTH CHILD was described according to voice and point of view. The conclusion is the narrator in the famous fiction of Doris Lessing’s was omniscient, heterodiegetic/non-character, overt and reliable in its voice. While the fiction was narrated with the shift of multifocalizers in the point of view both from a character, Harriet, who witnessed the events, and from a heterodiegetic narrator, who made comments and questions to focus the readers’ attention on what he narrates.